GLOMEROMYCOTA RECOVERED FROM CACAO SOIL - Kartini - Kramadibrata (REINWARDTIA, 2009)
KRAMADIBRATA, K. 2009. Glomeromycota recovered from cacao soil. Reinwardtia 12(5): 357–371.-Glomeromycotan fungi were studied from several cacao plantations in Indonesia (Java and Bali) and Ecuador. The identity of 28 species of Glomeromycota associated with cacao is presented.